The Methodology and Authentication of Deducing Based on the Alluded Implication from the Holy Quran - Sayyedeh Batool Ziyaoddin; Hasan Naqizadeh; Hasan Kharaghani; Morteza Norouzi (آموزه‌های قرآنی, 2019)
This article tries to examine the wisdom concept of the meaning of signification, position, pillar of the conditions and the realization, validity and validity of it, and the method of citation, description and analysis has been used. Investigations on the implication of the sign indicate that this kind of implication is not a kind of word but more that it is, it is of an inappriate nature and subjective argument, in terms of custom, purpose, but this interpretation is used with respect to God and the divine words, because God is the absolute being of all things. This sign has a degree defined by the definitions of jelly and hafi. this signification is obtained with rational precision and implies clear but in the sense of the same, the place of referencing refers to the punishment after the implication of necessity and argumentation. The signification of the signification of the verb of the appearances of the words is anatter of doubt, because neither in terms of application nor in the context of the dispute is the main purpose of the speaker and in other words, it is intended, but this signification can be considered as an implicit affair, and it is considered as the basis of rational interests. Referring to referring to the miracle of the Holy Qur'an, the Qur'anic jurisprudence is effective, and it can be used to derive religious laws, political rulings, beliefs and the like from the Qur'an.